2017
DOI: 10.1111/1745-5871.12205
|View full text |Cite
|
Sign up to set email alerts
|

Urban households' engagement in agriculture: implications for household food security in Ghana's medium sized cities

Abstract: Urban and peri-urban agriculture plays an important role in meeting the food and nutrition needs of those living in the increasingly urbanised cities in Africa. The extent and scope of the practise of urban and peri-urban agriculture differs from one city to another depending on the economic, environmental, socio-political, and contextual conditions at play. Using household data drawn from urban Techiman and Tamale in the Brong Ahafo and Northern regions of Ghana respectively, this paper descriptively analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Food systems are the result of complex human-environmental interactions that allow for the growing of food, processing, dissemination, and consumption by individuals [14]. Although food systems affect all people, they are often linked to rural communities.…”
Section: Urban Food Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food systems are the result of complex human-environmental interactions that allow for the growing of food, processing, dissemination, and consumption by individuals [14]. Although food systems affect all people, they are often linked to rural communities.…”
Section: Urban Food Systemsmentioning
confidence: 99%
“…Food systems are the result of coupled human and biophysical systems that are capable of providing food security, and institutions provide a manner in which these two systems may be bridged [14]. Broadly defined as both informal and formal entities that are created by humans in order to allocate power through sets of permissions and requirements [15], institutions play a critical role in the attainment of food security as a result of their influence in ensuring or undermining the availability of food by producers and the accessibility of food to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the damage caused by individual weather events, the larger climatic fluctuations expected from climate change will also reduce agricultural output. Population growth and urban expansion will put further pressure on Australia's agricultural system and food security, especially as much urban expansion occurs on productive agricultural land surrounding cities (James, 2014;Lawrence et al, 2013) and urban agriculture in Australia is not at the scale found in other countries (Ayerakwa, 2017). Population growth and urban expansion will put further pressure on Australia's agricultural system and food security, especially as much urban expansion occurs on productive agricultural land surrounding cities (James, 2014;Lawrence et al, 2013) and urban agriculture in Australia is not at the scale found in other countries (Ayerakwa, 2017).…”
Section: Relationship Between Food Security Climate Change and Backmentioning
confidence: 99%
“…They provide inexpensive and reliable sources of micronutrients and other nutrients essential for human health and contribute to the prevention of nutritional deficiency diseases [3][4][5]. In urban and peri-urban areas, vegetable production can improve food and nutritional security through increased dietary diversity and food consumption [6][7][8]. It is also a source of income and employment and contributes to livelihoods of many people in Africa [2,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In urban and peri-urban areas, vegetable production can improve food and nutritional security through increased dietary diversity and food consumption [6][7][8]. It is also a source of income and employment and contributes to livelihoods of many people in Africa [2,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%